Influence of alkali metallization (Li, Na and K) on photoluminescence properties of porous silicon - ESMER, KADİR (ELSEVIER SCIENCE BV, 2009)
We present results for alkali metallization effects on photoluminescence (PL) properties of porous silicon (PS). The metallization of PS was realized by immersion plating in solutions containing 3 mM LiNO3, KNO3 and NaNO3 metal salts. The surface bond configuration of PS was monitored by Fourier transmission infrared spectroscopy (FTIR) and it was found that the PS surface was oxidized after metallization. Surface properties of PS were investigated by field emission scanning electron microscopy (FE-SEM) and it was found that the PS surface was covered by alkali metals for short immersion times. The PL intensity increased for critical immersion times and PL spectrum shifted to high energy region with the metallization. The experimental results suggest a possibility that the metallization provides a relatively easy way to achieve an increase in the PL intensity and oxidation of the PS surface. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Porous silicon; Immersion plating; Electrochemical etching; Spectral response; LONG-TIME STABILIZATION; ENHANCEMENT; IRRADIATION; SURFACE; COPPER; DIODE; LAYER; IRON; AG